Fikih Mayoritas versus Fikih Minoritas: Melacak Akar Konflik Sosial atas Nama Syari’at - Ahmad Imam Mawardi (Justicia Islamica, 2012)
The basic character of fiqh is essentially relative, flexible and elastic. This character is visible when fiqh must adapt to social and cultural conditions of geographic areas that far from the birthplace of Islam. However, the basic character of fiqh is denied by some Muslim groups. They want to uniform fiqh according to their their interpretation that are considered more authentic and closer to the middle east fiqh format, centers the birth of Islam. The implication then is the "truth claims" which result in social conflicts in the name of religion. This paper is going to explore the argument how fiqh should be developed in accordance with Muslim plurality. This writing is framed in the context of dialog between the fiqh of majority and minority. The two of fiqh format often conflict and result social disharmony.